Synthesis of Geopolymer from Coal Fly Ash - Jha, Vinay Kumar; Budhamagar, Gautam Prasad (Journal of Nepal Chemical Society, 2013)
In the present work, geopolymers have been synthesized from coal fly ash (CFA) using NaOH and Na2SiO3 as activators. Some parameters like alkali concentration, amount of Na2SiO3 and curing time have been varied in order to improve the quality of geopolymeric product. The geopolymerization process has been performed using 3-8M NaOH solutions, Na2SiO3 to CFA mass ratios of 0.25-1.25 and curing time variation from 5-15 days. The curing temperature was fixed at 40ºC in all cases. In the variation of NaOH concentration, the maximum compressive strength of 2.3 MPa was obtained with CFA treated with 6M NaOH solution. Similarly during the variation of amount of Na2SiO3, the maximum compressive strength of 17.6 MPa was obtained with Na2SiO3 to CFA mass ratio of 1.25. Furthermore, the compressive strength was found increasing up to 20.3 MPa with increasing curing time. DOI: http://dx.doi.org/10.3126/jncs.v30i0.9331 Journal of Nepal Chemical Society Vol. 30, 2012 Page: 24-28 Uploaded date: 12/16/2013